Comparação de vazões em sifões obtidas por equações com vazões tabeladas - Sousa Neta, Maria do Céu Araújo de (Universidade Federal Rural do Semi-Árido, 2018)
Siphons are widely used equipment in industry and agriculture as well as in several other sectors of society. So studying your behavior is an essential part of her development. Thus, the present study was made of several comparisons, carried out through excel, between the results obtained by the formulas of forced conduits for tabulated flow values for polyethylene siphons. These values, in turn, were taken from tables composed in the "Irrigation Manual" and elaborated by the National Program for Rational Utilization of Irrigable Floors (PROVARZEAS). With the analysis of these values, it was observed that the use of the general equation of siphons resulted in flow values below the values found in the tables. And that the use of the equations of Swamee and Swamee-Jain provided, in general, flows equal to the tables.
Monografia
Keywords: Sifões; Vazões; Manual do irrigante; Fórmula de swame; Vazões reais; Siphons; Flows; Irrigation manual; Swame formula; Flow rates; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA